1993
DOI: 10.1164/ajrccm/147.2.301
|View full text |Cite
|
Sign up to set email alerts
|

Activated T-Lymphocytes and Macrophages in Bronchial Mucosa of Subjects with Chronic Bronchitis

Abstract: To examine the nature and the degree of leukocyte infiltration and to determine the state of activation of cells in bronchial mucosa of subjects with chronic bronchitis, bronchoscopy was performed in 10 subjects with a history of cigarette smoking and chronic sputum production and in six normal nonsmoking control subjects. Lobar bronchial biopsies were examined using histochemical and immunohistochemical techniques. Subjects with chronic bronchitis had an increased number of total leukocytes (CD45 positive cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
203
2
12

Year Published

1996
1996
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 331 publications
(233 citation statements)
references
References 25 publications
16
203
2
12
Order By: Relevance
“…The absence of any correlation between the number of neutrophils infiltrating the large airway subepithelium and increasing obstruction is consistent with previous studies which have reported no increase in neutrophils in the large [4,5,8,11] or the small airways [15,24] in subjects with COPD. The discordance of these results with those showing an increase in numbers of neutrophils and markers of neutrophil activation in bronchoalveolar lavage [10,11,13,14,25], induced sputum [26±28] and airway epithelium [29] remains to be explained.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The absence of any correlation between the number of neutrophils infiltrating the large airway subepithelium and increasing obstruction is consistent with previous studies which have reported no increase in neutrophils in the large [4,5,8,11] or the small airways [15,24] in subjects with COPD. The discordance of these results with those showing an increase in numbers of neutrophils and markers of neutrophil activation in bronchoalveolar lavage [10,11,13,14,25], induced sputum [26±28] and airway epithelium [29] remains to be explained.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have demonstrated an increase in the number of T-cells infiltrating the large airway subepithelium and a shift towards a CD8 phenotype [3±8] in addition to increases in the number of macrophages [4,5,8]. An increase in the number of infiltrating eosinophils has been observed in the large airway subepithelium although they do not appear to be degranulated as in asthma [9].…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…In chronic bronchitis, airway wall fibrosis has also been demonstrated [32,33]. The elevated levels of TGF-and FN released by AM from patients with chronic bronchitis may be of importance in the regulation of fibrosis, since airways macrophages are increased in numbers in the bronchial mucosa [13].…”
Section: Discussionmentioning
confidence: 97%
“…Increased numbers of CD8+ T-cells, alveolar macrophages and neutrophils are characteristic pathological features of the lungs in COPD [3,4]. Eosinophil numbers are increased during exacerbations and possibly also during stable phases in a subset of patients [5].…”
mentioning
confidence: 99%